Effect of external conditions and steam parameters on performance of combined-cycle power plants with back-pressure steam turbine; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Antonova A. M. Aleksandra Mikhailovna (2017, 2017)
Title screen